Correlation on Students Commitment and Satisfaction in Sekolah Tinggi Ilmu Ekonomi Galileo Batam Indonesia - Hazriyanto; Daus, Amir (International Journal of Psychosocial Rehabilitation, 2020)
Education at the college level is now supposed to get attention, especially related to the students who are in the college environment. The commitment and satisfaction of students who are in college are beneficial to create a college environment as expected. For that, a study needs to be run to investigate the commitment and satisfaction of students in a college environment, especially in the environment of Sekolah Tinggi Ilmu Ekonomi (STIE) Galileo Batam. Research is given attention to student commitment and satisfaction. This research is a quantitative study involving 33 respondents from students residing in the environment of STIE Galileo. The research aims to investigate the relationship between commitment and satisfaction. The questionnaire used to collect research data, then in sports with SPSS statistics. Correlation analysis is performed to ensure the relationship between commitment and satisfaction. The correlation test results showed that the relationship of commitment and satisfaction was positive and significant and the relationship is in a strong category. It is necessary to be noticed, and future research should consider other variables that are not explored in this research, such as motivation, environment, and more significant sample quantities and analysis tools such as; SEM SmartPLS and SEM Amos. In addition, future researchers can revisit from a demographic standpoint.